2023
DOI: 10.3389/fcvm.2023.1135723
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis, necroptosis and cuproptosis: Novel forms of regulated cell death in diabetic cardiomyopathy

Abstract: Diabetes is a common chronic metabolic disease, and its incidence continues to increase year after year. Diabetic patients mainly die from various complications, with the most common being diabetic cardiomyopathy. However, the detection rate of diabetic cardiomyopathy is low in clinical practice, and targeted treatment is lacking. Recently, a large number of studies have confirmed that myocardial cell death in diabetic cardiomyopathy involves pyroptosis, apoptosis, necrosis, ferroptosis, necroptosis, cuproptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 137 publications
0
5
0
Order By: Relevance
“…35,36 Furthermore Cuproptosis affects the course of Diabetic cardiomyopathy by destroying mitochondrial structure and function. 37 These ndings suggest that there may be underling correlation between CNN1 and AD through copper metabolism and Cuproptosis. But further studies are needed to clarify the speci c regulatory mechanisms.…”
Section: Discussionmentioning
confidence: 92%
“…35,36 Furthermore Cuproptosis affects the course of Diabetic cardiomyopathy by destroying mitochondrial structure and function. 37 These ndings suggest that there may be underling correlation between CNN1 and AD through copper metabolism and Cuproptosis. But further studies are needed to clarify the speci c regulatory mechanisms.…”
Section: Discussionmentioning
confidence: 92%
“…In particular the metabolic flux through glycolysis is partitioned [ 43 45 ], and mitochondrial bioenergetics and OxPhox are impaired, as well as lipid metabolism [ 43 , 46 48 ]. Moreover, accumulative researches have been demonstrated that cuproptosis play an important role as regulators of cell metabolism [ 49 51 ]. Therefore, this study conducted comprehensive analysis of the role of cuproptosis in ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…Ferroptosis has been identified in many pathological conditions, including cancer, COVID-19, and many other infectious, kidney, cardiac, and neurodegenerative diseases [ 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 ]. A different form of cell death with similar effects to ferroptosis is cuproptosis, where copper instead of iron is implicated in programmed cell death [ 205 , 206 , 207 , 208 , 209 , 210 , 211 ]. The inhibition by L1 of both iron- and copper-induced oxidative stress toxicity, is another unique property of the drug, which can be utilised for the design of new strategies and the development of new pharmaceuticals for the control of both ferroptosis and cuproptosis, which have been recognised in many diseases ( Figure 5 ).…”
Section: The High Clinical Antioxidant Potential Of Deferipronementioning
confidence: 99%